2015
DOI: 10.1086/681239
|View full text |Cite
|
Sign up to set email alerts
|

Doing Harm by Doing Good? The Negative Externalities of Humanitarian Aid Provision during Civil Conflict

Abstract: Humanitarian assistance is intended to ameliorate the human costs of war by providing relief to vulnerable populations. Yet, the introduction of aid resources into conflict zones may influence subsequent violence patterns and expose intended recipients to new risks. Herein, we investigate the potential negative externalities associated with humanitarian aid. We argue that aid can create incentives for armed actors to intentionally target civilians for violence. Aid incentivizes rebel violence by providing oppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(60 citation statements)
references
References 40 publications
1
53
1
Order By: Relevance
“…The lack of satisfaction and effectiveness at a macro level can be explained by taking into consideration the negative externalities of the micro-level aid relations (Wood and Sullivan 2015). If decisions of the recipient (government or NGO) are guided by its own (individual or organizational) profit-maximizing function and not necessarily by that of the entire society (nation), certain costs shall be paid by the "whole."…”
Section: Paragi Contemporary Gifts 000mentioning
confidence: 99%
“…The lack of satisfaction and effectiveness at a macro level can be explained by taking into consideration the negative externalities of the micro-level aid relations (Wood and Sullivan 2015). If decisions of the recipient (government or NGO) are guided by its own (individual or organizational) profit-maximizing function and not necessarily by that of the entire society (nation), certain costs shall be paid by the "whole."…”
Section: Paragi Contemporary Gifts 000mentioning
confidence: 99%
“…Instead of saying that insurgents become more powerful through looting, as most studies propose (e.g. Wood and Sullivan, 2015), this chapter suggests that corruption and the commensal relationship among local leaders, contractors, and insurgents can also explain the violence-inducing effect of aid in the case of Iraq. While the US military directly paid the Sunni sheikhs to buy down violence, local leaders contracted violence out to (foreign) fighters to induce more attacks.…”
Section: E V E L O P M E N T a I Dmentioning
confidence: 82%
“…Its effectiveness, however, has been a subject of debate among scholars and policy makers alike. While some empirical studies have shown that aid is effective in deterring or ending violent conflicts (Bazzi and Blattman, 2014;Collier and Hoeffler, 2002a;de Ree and Nillesen, 2009;Savun and Tirone, 2012), some have found it ineffective or, in some cases, counterproductive (Crost, Felter, and Johnston, 2014;Dube and Naidu, 2015;Narang, 2014;Narang, 2015;Nunn and Qian, 2014;Sollenberg, 2012;Wood and Sullivan, 2015).…”
Section: E V E L O P M E N T a I Dmentioning
confidence: 99%
See 2 more Smart Citations